Study of Bernard–Soulier Syndrome Megakaryocytes and Platelets Using Patient-Derived Induced Pluripotent Stem Cells - Mekchay, Ponthip; Ingrungruanglert, Praewphan; Suphapeetiporn, Kanya; Sosothikul, Darintr; Ji-au, Wilawan; Maneesri Le Grand, Supang; Israsena, Nipan; Rojnuckarin, Ponlapat (Thrombosis and Haemostasis, 2019)
Bernard–Soulier syndrome (BSS) is a hereditary macrothrombocytopenia caused by defects in the glycoprotein (GP) Ib-IX-V complex. The mechanism of giant platelet formation remains undefined. Currently, megakaryocytes (MKs) can be generated from induced pluripotent stem cells (iPSCs) to study platelet production under pharmacological or genetic manipulations. Here, we generated iPSC lines from two BSS patients with mutations in different genes (GP1BA and GP1BB: termed BSS-A and BSS-B, respectively). The iPSC-derived MKs and platelets were examined under electron microscopy and stained by immunofluorescence to observe proplatelet formation and measure platelet diameters which were defined by circumferential tubulin. BSS-iPSCs produced abnormal proplatelets with thick shafts and tips. In addition, compared with the normal iPSCs, the diameters were larger in platelets derived from BSS-A and BSS-B with the means ± standard deviations of 4.34 ± 0.043 and 3.88 ± 0.045 µm, respectively (wild-type iPSCs 2.61 ± 0.025 µm, p < 0.001). Electron microscopy revealed giant platelets with the abnormal demarcation membrane system. Correction of BSS-A and BSS-B-iPSCs using lentiviral vectors containing respective GP1BA and GP1BB genes improved proplatelet structures and platelet ultrastructures as well as reduced platelets sizes. In conclusion, the iPSC model can be used to explore molecular mechanisms and potential therapy for BSS.
Keywords: Bernard–Soulier syndrome; induced pluripotent stem cells; macrothrombocytopenia; megakaryocytes; platelets